ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA MATERI PELUANG - Irianti, Nathasa Pramudita; Setiawan, Rudy; Ate, Marlince Bali (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2022)
The purpose of this study in general is to determine the ability of students of SMP Sunan Giri Malang in understanding mathematical concepts. The specific objectives in this study, including: 1). Describing students' ability in understanding concepts on opportunity material, 2) Describing students' abilities in understanding concepts when solving problems. This research belongs to the type of qualitative descriptive research. Qualitative descriptive research was used to analyze the ability of eighth grade students of SMP Sunan Giri Malang in understanding the concept of opportunity. Data was collected through the methods of observation, tests, interviews and documentation. Furthermore, the data were analyzed descriptively qualitatively sequentially based on the question indicators, as follows; 1) Restate a concept, 2). Giving examples and not examples of a concept, 3). Presenting concepts in various forms of mathematical representation, 4). Grouping objects according to the properties, 5). Apply a concept or algorithm to problem solving. The results showed that the ability of class VIII students of SMP Sunan Giri Malang on the overall opportunity material got the following percentages: high ability category 47%, medium ability category 35% and low ability category 23%.